PENERAPAN LATIHAN FISIK DAN DZIKIR UNTUK MENURUNKAN NYERI PADA LANSIA DENGAN HIPERCOLESTEROLEMIA - Rosmin Ilham; Sri Yulan Hunowu; Sitti Fadhilah Mawaddah Soleman (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypercholesterolemia occurs due to high blood fat traction, namely in the form of increased total and LDL cholesterol levels and decreased HDL levels. If let for a long time, cholesterol will stick to the walls of blood vessels and cause the walls of blood vessels to become stiff. Purpose of the study to determine the effectiveness before and afteer thee application of phycal exercise and dzikir in reducing pain with hypercholesterolemia in the elderly. Researce using describes a particular process or problem situation observed. Based on the research in the table obtained cholesterol in the elderly after the application of physical eexercise is that on client 1 there is decrease in cholesterol pain from 5 to4. Client 2 there is a decrease in cholesterol pain from 5 to 4 and client 3 there is decreasee in cholesterol pain and 6 to 5. So in these three cases the client experienced reduction of cholesterol levels the conclusion of the application of physical exercise and dzikir to reduce pain in the elderly with hiypercholesterolemia at the Griya Lansia Jannati Hame in 2022 cholesterol pain in the elderly before the application of physical exercise and dzikir men 2 has a decline from 5 men to 4, and lan 3 has decline from 6 men to 5